2021
DOI: 10.7150/jca.51749
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Factors of Establishing Patient-derived Tumor Model

Abstract: Establishing an applicable preclinical model is vital for translational cancer research. Patient-derived xenograft has been important preclinical model systems and widely used for cancer research. Patient-derived xenograft models that represent the tumors of the patients are necessary to better translate research discoveries and to test potential therapeutic approaches. However, research in this field is hampered by the limited engraftment rate. In this review, we go over a large number of researches on patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 79 publications
(84 reference statements)
5
36
0
Order By: Relevance
“…A prolonged implantation time causes tissue metabolism, resulting in a lower engraftment rate [28,29,[34][35][36]50]. The volume of sample should be a certain amount for engraftment [11]. Hoffmann et al reported that no engraftment was detectable when using tumor pieces that were solid 3-to 5-mm cubes [28].…”
Section: Treatment Of Specimensmentioning
confidence: 99%
See 4 more Smart Citations
“…A prolonged implantation time causes tissue metabolism, resulting in a lower engraftment rate [28,29,[34][35][36]50]. The volume of sample should be a certain amount for engraftment [11]. Hoffmann et al reported that no engraftment was detectable when using tumor pieces that were solid 3-to 5-mm cubes [28].…”
Section: Treatment Of Specimensmentioning
confidence: 99%
“…However, the different types of mice described above are used in diverse cancers. This means that use of a suitable type of mouse improves the engraftment rate [11]. For example, nude mice were used for PDX of gastric cancer.…”
Section: Mouse Strainsmentioning
confidence: 99%
See 3 more Smart Citations